Antitumor Effects of Evodiamine in Mice Model Experiments: A Systematic Review and Meta-Analysis - Cong Yin (Frontiers Media S.A., 2021)
BackgroundEvodiamine (EVO), an alkaloid extracted from the traditional Chinese medicine Euodia rutaecarpa, plays an important role in the treatment of cancer. This study was performed to clarify the effects of evodiamine in mice tumor model studies.MethodsElectronic databases and search engines involved China Knowledge Resource Integrated Database (CNKI), Wanfang Database, Chinese Scientific Journal Database (CSJD-VIP), China Biomedical Literature Database (CBM), PubMed, Embase, Web of Science, and ClinicalTrials.gov databases, which were searched for literature related to the antitumor effects of evodiamine in animal tumor models (all until 1 October 2021). The evodiamine effects on the tumor volume and tumor weight were compared between the treatment and control groups using the standardized mean difference (SMD).ResultsEvodiamine significantly inhibited tumor growth in mice, as was assessed with tumor volume [13 studies, n=267; 138 for EVO and 129 for control; standard mean difference (SMD)= -5.99; 95% (CI): -8.89 to -3.10; I2 = 97.69%, p ≤ 0.00], tumor weight [6 studies, n=89; 49 for EVO and 40 for control; standard mean difference (SMD)= -3.51; 95% (CI): -5.13 to -3.90; I2 = 83.02%, p ≤ 0.00].ConclusionEVO significantly suppresses tumor growth in mice models, which would be beneficial for clinical transformation. However, due to the small number of studies included in this meta-analysis, the experimental design and experimental method limitations should be considered when interpreting the results. Significant clinical and animal studies are still required to evaluate whether EVO can be used in the adjuvant treatment of clinical tumor patients.